The range and reach of qualitative research in neurosurgery: A scoping review - Charlotte J. Whiffin; Kathleen Joy O. Khu; Brandon G. Smith; Isla Kuhn; Santhani M. Selveindran; Laura Hobbs; Samin Davoody; Yusuf Docrat; Orla Mantle; Upamanyu Nath; Lara Onbaşı; Stasa Tumpa; et al. (PLoS ONE, 2025)
Following calls for more qualitative research in neurosurgery, this scoping review aimed to describe the range and reach of qualitative studies relevant to the field of neurosurgery and the patients and families affected by neurosurgical conditions. A systematic search was conducted in September 2024 across six databases: Medline via Ebsco; Embase via OVID; PsycINFO via Ebsco; Scopus; Web of Science Core Collection; and Global Health via Ebsco. Eligibility criteria were based on Population, Concept, and Context. The search identified 18,809 hits for screening with 812 included in the final analysis. Seven themes were identified from a content analysis of study aims: 1 Perspectives of living with a neurosurgical condition; 2 Family perspectives; 3 Perceptions of neurosurgery; 4 Perceptions of general healthcare care; 5 Decision making; 6 Advancing neurosurgery; and, 7 Understanding neurosurgical conditions. Traumatology was identified as the most researched sub-specialty (43.2%) yet few studies were led explicitly by a neurosurgeon (1.6%) or those with a neurosurgical affiliation (10.5%). Lead authors were predominantly from high income countries (93.7%), as were most multi-author teams (86.6%). There was a trend towards increasing publication over time; however, only 8.4% of papers were published in neurosurgical specific journals. The data set had an average Field Weighted Citation Impact of 0.96 and Field Weighted Views Impact of 1.11, 18.9% were cited in policy documents in 15 countries. This scoping review provides a comprehensive picture of the current qualitative research base in neurosurgery and suggests ways to improve the conduct and reporting of such studies in the future. Addressing these challenges is crucial if qualitative research is to advance the neurosurgical evidence base in a rigorous way.